Covid-19 Pandemic and Students Performance in Selected Secondary Schools in Rukungiri District. - Ainemigisha, Prossy (Kabale University, 2024)
The study focused on the impact of the COVID-19 pandemic on students' performance in selected secondary schools in Rukungiri District. Conducted in three randomly chosen secondary schools, the study aimed to: investigate the pandemic's impact on students' academic performance, examine the influence of remote learning modalities implemented during the pandemic, and identify and analyze socio-economic and psychological factors affecting students' academic performance during this period. The researcher employed a descriptive survey design to collect data, which provided a detailed description of the schools and respondents involved. Out of a total sample of 539 participants, 500 took part in the study. Data collection methods included both questionnaires and interviews. The data were analyzed using qualitative and quantitative techniques and presented in tables, frequencies, and percentages. The findings highlighted the critical role of transitioning to digital platforms, stressing the need for educational institutions to ensure the quality and effectiveness of online instructional methods, in line with literature on the challenges of global crises. The researcher concluded that recognizing psychological well-being as a key factor influencing academic performance is consistent with the growing literature on the pandemic's psychosocial impact on students. Issues like stress, anxiety, and mental health problems, intensified by the pandemic's uncertainty and disruption, have contributed to difficulties in concentration and academic engagement. The researcher recommended initiatives to bridge the digital divide by ensuring equitable access to technology for all students, including providing devices and reliable internet connectivity to those in need.